IMPLIKASI HUKUM ATAS PELANGGARAN HAK CIPTA TERHADAP KONTEN CREATOR DI SOSIAL MEDIA - Danang Permadi; Hisam Asngari (Institut Agama Islam Hasanuddin Pare, 2025)
The digital era has given rise to a new profession: content creators, who utilize social media as a primary platform for their work. However, the ease of access and dissemination of information on social media also opens wide opportunities for copyright infringement. This study aims to examine in-depth the legal implications arising from copyright infringement of content creators' works on social media, as well as to analyze the effectiveness of existing legal protections. The research methods used were literature review and analysis of legislation, specifically Law Number 28 of 2014 concerning Copyright. The results indicate that copyright infringement of content creators is subject to criminal and civil penalties. However, law enforcement is often hampered by several factors, such as the difficulty of providing evidence, cross-border jurisdiction, and low public legal awareness. This study recommends the need for extensive legal education for the public and content creators, as well as optimizing the role of social media platforms in protecting their users' copyright. This will enable the creative industry ecosystem on social media to grow healthily and sustainably.